Anti-biofilm efficacy of 100 MeV gold ion irradiated polycarbonate against Salmonella typhi. (December 2017) - Joshi, R.P.; Hareesh, K.; Bankar, A.; Sanjeev, G.; Asokan, K.; Kanjilal, D.; Dahiwale, S.S.; Bhoraskar, V.N.; Dhole, S.D.
Abstract: Polycarbonate (PC) films were irradiated by 100 MeV gold (Au 7+ ) ions and characterized to study changes in its optical, chemical, surface morphology and thermal properties. UV–Visible spectroscopic results revealed the decrease in the optical band gap of PC after ion irradiation due to chain scission mainly at the carbonyl group which is corroborated by Fourier Transform Infrared spectroscopic results. X-ray diffractogram study showed decrease in crystallinity of PC film after irradiation. Scanning electron microscopic results showed the micropores formation in PC which results in surface roughening. Differential scanning calorimetric results revealed decrease in glass transition temperature indicating the decrease in molecular weight of PC corroborated by rheometric studies. PC films irradiated by 100 MeV Au 7+ ions showed increased anti-biofilm activity against the human pathogen, Salmonella typhi ( S. typhi ). Morphology of S. typhi was changed due to stress of Au 7+ irradiated PC. Cells length was increased with increasing fluences. The average cell length, cell volume and surface area was increased significantly (P<0.05) with increasing ion fluences. Biofilm formation was inhibited ≈ 20% at lower fluence and 96% at higher fluence, which observed to be enhanced anti-biofilm activity in Au 7+ irradiated PC. Highlights: 100 MeV gold (Au 7+ ) ions irradiated on Polycarbonate (PC) films. Optical, chemical, surface morphology and thermal properties are investigated. Salmonella typhi cell length, volume and area increases with increase in fluences.